Peran Bhabinkamtibmas dalam Melakukan Penanggulangan Kejahatan di Wilayah Hukum Polrestabes Medan - Muhammad Raihan Rizqullah; Rizkan Zulyadi; Isnaini Isnaini (Mahesa Research Center, 2022)
The purpose of this study was to determine the legal setting, inhibiting factors and the role of Bhabinkamtibmas in Combating Crime in the jurisdiction of the Medan Polrestabes. The research method used in this study is normative juridical research with a statutory and conceptual approach, while the data collection instruments use observation, documentation studies and interviews. While the data analysis is descriptive analysis. The results of this study indicate that: The legal arrangements that regulate Bhabinkantibmas include Law No. 2 of 2002 concerning the Indonesian National Police, Regulation of the National Police Chief No. 3 of 2015 concerning Community Policing, and the Decree of the Chief of Police No. Pol : SKEP/737/X/2005 October 15, 2005 Regarding Policies and Strategies for Implementing Community Policing Models. Factors that can hinder crime prevention are influenced by several things, including the organizational structure of Bhabinkamtibmas Polrestabes Medan, human resource factors, budget factors, facilities and infrastructure factors, and community attention and support factors. Its role is to carry out preventive crime prevention actions through the implementation of the Community Police (Polmas) program, the Door to Door System Program and carry out Repressive Crime Prevention Actions through the Problem Solving Program.